Metabolomics Based Identification of SIRT5 and Protein Kinase C Epsilon Regulated Pathways in Brain - Koronowski, Kevin B.; Khoury, Nathalie; Morris-Blanco, Kahlilia C.; Stradecki-Cohan, Holly M.; Garrett, Timothy J.; Perez-Pinzon, Miguel A. (Frontiers in Neuroscience, 2018)
The role of Sirtuins in brain function is emerging, yet little is known about SIRT5 in this domain. Our previous work demonstrates that protein kinase C epsilon (PKCε)-induced protection from focal ischemia is lost in SIRT5-/- mice. Thus, metabolic regulation by SIRT5 contributes significantly to ischemic tolerance. The aim of this study was to identify the SIRT5-regulated metabolic pathways in the brain and determine which of those pathways are linked to PKCε. Our results show SIRT5 is primarily expressed in neurons and endothelial cells in the brain, with mitochondrial and extra-mitochondrial localization. Pathway and enrichment analysis of non-targeted primary metabolite profiles from Sirt5-/- cortex revealed alterations in several pathways including purine metabolism (urea, adenosine, adenine, xanthine), nitrogen metabolism (glutamic acid, glycine), and malate-aspartate shuttle (malic acid, glutamic acid). Additionally, perturbations in β-oxidation and carnitine transferase (pentadecanoic acid, heptadecanoic acid) and glutamate transport and glutamine synthetase (urea, xylitol, adenine, adenosine, glycine, glutamic acid) were predicted. Metabolite changes in SIRT5-/- coincided with alterations in expression of amino acid (SLC7A5, SLC7A7) and glutamate (EAAT2) transport proteins as well as key enzymes in purine (PRPS1, PPAT), fatty acid (ACADS, HADHB), glutamine-glutamate (GAD1, GLUD1) and malate-aspartate shuttle (MDH1) metabolic pathways. Moreover, PKCε activation induced alternations in purine metabolites (urea, glutamine) that overlapped with putative SIRT5 pathways in WT but not in SIRT5-/- mice. Finally, we found that purine metabolism is a common metabolic pathway regulated by SIRT5, PKCε and ischemic preconditioning. These results implicate Sirt5 in the regulation of pathways central to brain metabolism, with links to ischemic tolerance.